Antioxidant and Antibacterial Evaluation of Novel Azolidine-4-one Derivatives Synthesized from Creatinine - Salom, Khawla Jabar; Khalaf, Muna Ismael (Iraqi Journal of Science, 2026)
In this study, new azolidine-4-one derivatives were synthesized using creatinine as starting materials. Initially, Schiff bases were formed through the reaction of creatinine, acting as a primary amine, with various aromatic aldehydes. This scaffold proved to be valuable for the development of new biologically active molecules. The resulting Schiff bases (1–5) were subsequently reacted with glycine, thioglycolic acid, and glycolic acid in ring-closing reactions to generate new compounds (6–10), (11–15), and (16–20), respectively. The structures of the new compounds were confirmed using the FT-IR and further characterized using1HNMR. The biological activities and antioxidant capacity of some synthesized compounds have been studied in vitro with promising results. The new compounds showed improved antioxidant effects compared to the parent compounds.